Biophysical characterization and structure of the Fab fragment from the NIST reference antibody, RM 8671. (November 2017) - Karageorgos, Ioannis; Gallagher, Elyssia S.; Galvin, Connor; Gallagher, D. Travis; Hudgens, Jeffrey W.
Abstract: Monoclonal antibody pharmaceuticals are the fastest-growing class of therapeutics, with a wide range of clinical applications. To assure their safety, these protein drugs must demonstrate highly consistent purity and stability. Key to these objectives is higher order structure measurements validated by calibration to reference materials. We describe preparation, characterization, and crystal structure of the Fab fragment prepared from the NIST Reference Antibody RM 8671 (NISTmAb). NISTmAb is a humanized IgG1κ antibody, produced in murine cell culture and purified by standard biopharmaceutical production methods, developed at the National Institute of Standards and Technology (NIST) to serve as a reference material. The Fab fragment was derived from NISTmAb through papain cleavage followed by protein A based purification. The purified Fab fragment was characterized by SDS-PAGE, capillary gel electrophoresis, multi-angle light scattering, size exclusion chromatography, mass spectrometry, and x-ray crystallography. The crystal structure at 0.2 nm resolution includes four independent Fab molecules with complete light chains and heavy chains through Cys 223, enabling assessment of conformational variability and providing a well-characterized reference structure for research and engineering applications. This nonproprietary, publically available reference material of known higher-order structure can support metrology in biopharmaceutical applications, and it is a suitable platform for validation of molecular modeling studies.